PENGARUH INSENTIF PAJAK, FINANCIAL DISTRESS DAN EARNING PRESSURE TERHADAP KONSERVATISME AKUNTANSI - Arya; Raphael, Alexander (Jurnal Nusa Akuntansi, 2025)
This research aims to determine and test the influence of Tax Incentives, Financial Distress and Earning Pressure on Accounting Conservatism. By using an associative quantitative type, the population used in this research was 125 companies with a purposive sampling sample selection method of 20 companies with a total of 100 observation data. This research uses three independent variables, namely Tax Incentives, Financial Distress and Earning Pressure, while the dependent variable is Accounting Conservatism. The test used is panel data regression analysis using the Eviews version 12 program. The results of this research show that Tax Incentives, Financial Distress and Earning Pressure are together have a simultaneous effect on company value, and Financial Distress and Earning Pressure do not have a partial effect on Accounting Conservatism, Tax incentives has a significant effect on Accounting Conservatism.